2009
DOI: 10.1007/s00330-009-1411-9
|View full text |Cite
|
Sign up to set email alerts
|

Adequate image quality with reduced radiation dose in prospectively triggered coronary CTA compared with retrospective techniques

Abstract: The goal of our study was to compare a prospective triggering (PT) CT technique with retrospectively gated (RG) CT techniques in coronary computed tomographic angiograms (CCTA) with respect to image quality and radiation dose. Sixty consecutive patients were enrolled. CCTAs using the RG technique were obtained with a dual-source 64-slice CT system in 40 patients, using ECG-triggered tube current modulation, with either a broad pulsing window at 30-80% of the RR interval (group RGb, 20 patients, heart rate > 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 35 publications
4
37
0
1
Order By: Relevance
“…(2,(5)(6)(7)(8)(9)14,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) The attrition diagram for our study depicting the search process is shown in Fig. 2 Table III.…”
Section: Resultsmentioning
confidence: 99%
“…(2,(5)(6)(7)(8)(9)14,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) The attrition diagram for our study depicting the search process is shown in Fig. 2 Table III.…”
Section: Resultsmentioning
confidence: 99%
“…Arnoldi et al (15) demonstrated that when using prospective scanning, the required radiation dose is 2.8 mSv, which is markedly lower than the retrospective scanning dose of 18.4 mSv. A prospective series scan is a step-axis scanning mode, Table II.…”
Section: Discussionmentioning
confidence: 99%
“…There are two levels of ECG-controlled tube current modulation available, whereby the tube output can be reduced to 25% or 4% (min-dose, Siemens Healthcare, Forchheim, Germany) outside the predefined temporal window [7,8,20]. The former (i.e.…”
Section: Imaging Techniquementioning
confidence: 99%
“…It is advocated when performing cardiovascular CT on children with heart rate above 80 bpm, that data is acquired at end-systole using an absolute (ms) trigger delay as opposed to a relative (percentage) trigger delay [8,[18][19][20] to ensure maximum image quality. This will also help minimise stair-step artefact.…”
Section: Imaging Techniquementioning
confidence: 99%
See 1 more Smart Citation